Stereoretentive Copper‐Catalyzed Directed Thioglycosylation of C(sp2)−H Bonds of Benzamides. Issue 42 (25th August 2016) - Chabrier, Amélie; Bruneau, Alexandre; Benmahdjoub, Sara; Benmerad, Belkacem; Belaid, Sabrina; Brion, Jean‐Daniel; Alami, Mouâd; Messaoudi, Samir
Abstract: An efficient thioglycosylation of C(sp 2 )−H bonds with thiosugars has been established for the first time. Using only Cu(OAc)2 ⋅H2 O as a catalyst and Ag2 CO3 as an additive in DMSO, the protocol proved to have broad scope, and a variety of complex thioglycosides have been prepared in good yields with exclusive β‐selectivity. Abstract : Pour some thiosugar on CH : An efficient thioglycosylation of C(sp 2 )−H bonds with thiosugars has been established for the first time. Using only Cu(OAc)2 ⋅H2 O as a catalyst and Ag2 CO3 as an additive in DMSO, the protocol proved to have broad scope, and a variety of complex thioglycosides have been prepared in good yields with exclusive β‐selectivity (see scheme).